The Influence of Virtual Reality on the Traditional Marketing Mix Elements in the Architectural Industry: A Study in Saudi Arabia - ALHEIASAT, ABDALLAH MOH'D ISLAM AHMAD (İstanbul Kültür Üniversitesi, 2024)
This research presents a better understanding of the influence of virtual reality adoption on the traditional marketing mix elements 4Ps (product, price, place, and promotion) in the architectural industry in Saudi Arabia. The research investigates how Virtual Reality influences these marketing elements, aiming to enhance project outcomes and client satisfaction. Four hypotheses were formulated to assess VR's effect on each marketing component. The research targeted architectural companies in Saudi Arabia, diverse in services ranging from design to construction. Due to the challenge in specifying the number of active firms, a representative sample was chosen using non-probability convenient sampling, as geographical constraints necessitated quick and practical data collection. Following established research guidelines, a sample size of at least 400 respondents was determined adequate, aligning with the "10:1" rule for regression analysis. Data was collected through an online questionnaire completed by 400 participants, ensuring comprehensive responses with mandatory answer fields. The questionnaire, informed by prior validated tools and literature, covered aspects of virtual reality adoption and marketing strategies, providing a robust dataset for analysis. This study suggests incorporating VR into the architectural marketing mix can lead to more effective marketing strategies, improved project visualization, and enhanced client interaction. The study validates each hypothesis, demonstrating VR's transformative potential across all aspects of the marketing mix. Future research may delve into the long-term benefits of VR on customer satisfaction, the integration of VR with other emerging technologies, and comparative studies across different regions and cultural contexts to fully harness VR's potential in the architectural industry.
Sanal Gerçekliğin Mimarlık Sektöründe Geleneksel Pazarlama Karması Unsurları Üzerindeki Etkisi: Suudi Arabistan'da Bir Araştırma
Yüksek lisans tezi.
Keywords: Virtual Reality Adoption; Marketing Mix; Product; Place; Price; Promotion